2006
DOI: 10.2353/ajpath.2006.051320
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic Acid-Enriched Diet Prevents Myocardial Damage and Expands Longevity in Cardiomyopathic Hamsters

Abstract: Randomized clinical trials have demonstrated that the increased intake of -3 polyunsaturated fatty acids significantly reduces the risk of ischemic cardiovascular disease, but no investigations have been performed in hereditary cardiomyopathies with diffusely damaged myocardium. In the present study, ␦-sarcoglycan-null cardiomyopathic hamsters were fed from weaning to death with an ␣-linolenic acid (ALA)-enriched versus standard diet. Results demonstrated a great accumulation of ALA and eicosapentaenoic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 62 publications
3
46
2
Order By: Relevance
“…7,18 Fiaccavento et al noted that omega-3 PUFA prolonged survival and inhibited myocardial pathologies in hamsters with cardiomyopathy. 10 To our knowledge no studies have been done to evaluate the effect of omega-3 supplementation on echocardiographic parameters in CHF patients. We investigated the effect of 2 g/day of omega-3 on echocardiographic parameters in patients with class II or III heart failure due to ischemic causes.…”
Section: Discussionmentioning
confidence: 99%
“…7,18 Fiaccavento et al noted that omega-3 PUFA prolonged survival and inhibited myocardial pathologies in hamsters with cardiomyopathy. 10 To our knowledge no studies have been done to evaluate the effect of omega-3 supplementation on echocardiographic parameters in CHF patients. We investigated the effect of 2 g/day of omega-3 on echocardiographic parameters in patients with class II or III heart failure due to ischemic causes.…”
Section: Discussionmentioning
confidence: 99%
“…20 -24 The present investigation has shown that an ALA-enriched diet i) precludes myocyte and muscular tissue damage in ␦-SG-null dystrophic hamsters, and ii) modulates satellite cells proliferation promoting myogenic differentiation. The skeletal muscle damage, similarly to hereditary cardiomyopathy, 13,20,[21][22][23][24] is prevented by modifying plasmalemma biophysical properties and membrane signaling to the intracellular compartment.…”
mentioning
confidence: 99%
“…This compound belongs to the group of omega-3 fatty acids, commonly occurring in flaxseed, canola oil, soybeans, and walnut oils (Simopoulos 2004;Gruenwald et al 2004). Oils rich in a-linolenic acid are used to prevent and treat heart diseases, an elevated level of cholesterol and triglycerides in blood, and hypertension (Fiaccavento et al 2006;Brouwer et al 2004). 1,2-Benzenedicarboxylic acidphthalic acid was identified in fresh, white and red Panax ginseng Abd El-Aty et al (2008), as well as in crude extracts of Alpinia galanga (L.) Willd (Rao et al 2010).…”
Section: Resultsmentioning
confidence: 99%